1980
DOI: 10.1677/joe.0.0860001
|View full text |Cite
|
Sign up to set email alerts
|

Macropodid Marsupial Luteinizing Hormone: Validation of Assay Procedures and Changes in Concentrations in Plasma During the Oestrous Cycle in the Female Tammar Wallaby (Macropus Eugenii)

Abstract: A heterologous double antibody radioimmunoassay employing a rabbit anti-ovine LH antiserum (GDN no. 15) has been developed for the assessment of concentrations of LH in macropodid marsupial pituitary extracts and plasma. In this radioimmunoassay system highly purified ovine, rat human and kangaroo LH preparations demonstrated apparently parallel dose-response curves, as did serial dilutions of crude pituitary extracts from a wide range of Austrlian marsupial species and serial dilutions of plasma from ovariect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 18 publications
(27 reference statements)
3
20
0
Order By: Relevance
“…Associated events all occur within 24 h: the oestradiol peak after 8-3 h, oestrus after 9-8 h, and the LH surge after 15 h. The intervals from progesterone drop to mating and to the LH surge are very similar to the interval from birth to mating of 8 0 h and the interval from birth to LH peak of 160 h reported by Tyndale-Biscoe et al (1983), and the interval from birth to mating is the same as that reported by Shaw & Renfree (1984). The interval from LH surge to ovulation, now shown to be very close to 24 h, refines the estimate of 20-40 h by Sutherland et al (1980).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Associated events all occur within 24 h: the oestradiol peak after 8-3 h, oestrus after 9-8 h, and the LH surge after 15 h. The intervals from progesterone drop to mating and to the LH surge are very similar to the interval from birth to mating of 8 0 h and the interval from birth to LH peak of 160 h reported by Tyndale-Biscoe et al (1983), and the interval from birth to mating is the same as that reported by Shaw & Renfree (1984). The interval from LH surge to ovulation, now shown to be very close to 24 h, refines the estimate of 20-40 h by Sutherland et al (1980).…”
Section: Discussionsupporting
confidence: 88%
“…Parturition coincides with a transient pulse of prolactin (Hinds & Tyndale-Biscoe, 1982a) and a very rapid decline of progesterone in peripheral plasma from 500 to less than 200 pg/ml (Hinds & Tyndale-Biscoe, 1982b) and is associ¬ ated with a decline in progesterone content of the corpus luteum (CL) of pregnancy (Renfree, Green & Young, 1979). Oestrus and a transient pulse of luteinizing hormone (LH) occur 8 and 16 h, respectively, after parturition (Tyndale-Biscoe, Hinds, Horn & Jenkin, 1983), and ovulation occurs between 20 and 48 h after the LH pulse (Sutherland, Evans & Tyndale-Biscoe, 1980). Tyndale-Biscoe et al (1983) considered that the decline in progesterone might initiate this sequence of events through an alteration of the progesterone:oestrogen ratio, but they were unable to deter¬ mine the role of oestradiol at that time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparative studies that characterize LH surge in marsupials are limited to the Tammar wallaby (Macropus eugenii; Sutherland et al 1980), kowari (Dasyuroides byrnie; Fletcher 1983) and brushtail possum (Trichosurus vulpecula;Fletcher and Selwood 2000). In M. eugenii (Sutherland et al 1980), the LH surge occurs 8 h after oestrus and is followed by ovulation 24 -48 h later. Unusually, D. byrnie (Fletcher 1983) females demonstrate a LH peak 12 days before oestrus; its significance to ovulation remains ambiguous.…”
Section: Introductionmentioning
confidence: 99%